Students' Understanding of Article Writing Process in the Fourth Semester of English Department of University of Islam Malang - Heni Nur Chumaidah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Writing is a form of communication besides spoken form that should be mastered by the students, especially writing article. Writing article can help the students to think critically. But, before writing article, students should understand the article writing process first. This research was about the students’ understanding of article writing process in the fourth semester. This research was conducted at University of Islam Malang with two students from English Department who had finished Writing IV course and had a high score in Writing IV course. The research design was descriptive qualitative. The data was obtained by conducting a group interview session with 16 open-ended questions that were adapted from previous research, then the data was analyzed qualitatively using thematic analysis. The result of this research showed that the participants had a good understanding of article writing process. It was proven by their clear and detailed explanation about article writing process. However, the participants still faced some difficulties in article writing process in terms of making indirect quotation and limited time in learning. From this study, there were some suggestions about several things that should be improved. For future researchers, it is suggested to conduct the same research that more focused on the students’ difficulties on article writing process and how to solve it